Psychology from the Islamic perspective. By Aisha Utz. Riyadh: International Islamic Publishing House, 2011, pp. 351. ISBN: 978-603-501-108-2 (Paperback) - Abdul Razak, Abdul Latif (IIUM Press, 2012)
Psychology from the Islamic Perspective is a long awaited book that helps in satisfying the long quest endured by Muslim psychologists. Quite often, materials in this field are written from secular perspective. The author begins her book by clearly stating its objectives namely, to describe and detail Islamic perspectives on psychology, mental health and well-being, to present a number of contemporary scientific evidences that verify the miracles of the Qur’ān and to further remind readers of the potential for self-transformation that Islam offers. In line with these objectives, the author adopts an analytical and descriptive methodology.